Isolamento e a caracterização de fungos endofíticos de Virola Venosa (Poepp. Ex A. DC) Warb. com potenciais de atividades biológicas - Fernandes, Kamila Rangel Primo (2015)
The research of endophytic fungi, especially those present in tropical species, is an innovative field in the discovery of new drugs. There are no studies on the endophytic microbiota Virola venosa species the research in question provides information from the host as from their endophytic isolates. The objective of this study was to investigate the antimicrobial activity and evaluate the antioxidant potential of endophytic fungi isolated from V. venosa and their plant extracts. It was carried out the isolation and characterization of endophytic fungus from V.venosa parts. It has been investigated phenolic compounds and flavonoids based on previous phytochemical selection (Screening) extracts of plants. For this, it was collected in Manaus Amazonas (latitude: 3. 6,058`S longitude: 59. 58,459`W), branches, leaves and stem V. venous both to obtain the hexane extracts, ethyl acetate and methanol, as for the isolation of endophytic fungi. 105 isolates were obtained and distributed into 16 groups, considering their macromorphological characteristics that reveal the probable presence of genres such as Phomopsis, Xylaria, Penicillium and yeasts. In the antioxidant activity assays represented results in crude extracts stem methanol 84% DPPH capture, 13,4 μg/mL IC50, leaf methanol 85% capture IC50 30 μg/mL, stem ethyl acetate has shown 84,1% of the free radical capture and DPPH IC50 equal to 34,7μg/mL. The antimicrobial activity tests were carried out using as test strains the bacteria Escherichia coli, Pseudomonas aureuginosa, Staphylococcus aureus, Enterococcus faecalis and Candida albicans, which the relevant plant extracts of leaves and stems in methanol inhibited the growth of Pseudomonas aureuginosa at a concentration of crude leaf extract 500 μg/ml in methanol and stem 125 μg/ml. For fungal extracts, there was inhibition of Candida albicans from 7,8 μg/ml on a fermented crude extract of a Colletotrichium and 15,6 μg/ml crude extract of mycelium of a Peniciullium, both presented fungistatic reaction. It is important to point out that the studies conducted here show the correlation between the results of the tests and the diversity of fungi existent on the host. Also the correlation between the results of its plant extracts. All of this with the intention of seeking information about the potential that endophytic fungi of Virola venosa have for biotechnology. Key words: Virola venosa, Endophytic fungi, Antioxidant, Antimicrobial